Effects of Hatha yoga on cognitive functions in the elderly: a cross-sectional study. Issue 1 (31st December 2022) - Baklouti, Souad; Aloui, Asma; Baklouti, Hana; Souissi, Nizar; Jarraya, Mohamed
Abstract: This study aimed to investigate the effects of Hatha yoga practice on cognitive functions in the elderly. Thirty healthy older men participated in this study. They belonged to 2 groups. The first group included 15 Hatha yoga practitioners for at least 2 years. The control group involved 15 male older adults who shared the same characteristics (age, years of formal education, and level of physical activity) as the Hatha yoga group but were naive to yoga, meditation, or any mind-body intervention. Neuropsychological tests were applied to measure selective attention, sustained attention, episodic memory, and processing speed. The following tests were administered: The French adaptation of the Victoria Stroop test, the Zazzo's Cancellation Task, the Five Word Test, and a battery of computerized tests to evaluate reaction time. Long-term Hatha yoga practice showed promising results related to executive functions and reaction time, but no significant difference was found between the two groups in episodic memory and sustained attention although a trend of improvement was observed in favor of Hatha yoga practitioners. In conclusion, long-term Hatha yoga practitioners have better cognitive abilities compared to the control group in certain aspects of cognitive functions. Further physiological and psychological variables need to be examined in order to highlight the correlation between yoga intervention and cognitive performance.